Regulation of Toll-Like Receptor Expression in Human Conjunctival Epithelial Cells. (25th May 2014) - Li, Jing; Setiawan, Melina; Wu, Hong; Beuerman, Roger W.; Zhao, Peiquan
Abstract : Previous studies showed marked decrease of multiple Toll-like receptor (TLR) expression in corneal and conjunctival epithelial cells upon culture in vitro. The aim of this study was to identify factor(s) which regulate TLR expression. Primary human conjunctival epithelial cells and immortal conjunctival (IOBA-NHC) and corneal epithelial cell lines (HCET) were used. The effect of various cytokines, hypoxia, mechanical wounding, and airlifting culture on TLR expression was examined by quantitative PCR and western blot analysis. Ligand stimulated TLR activation was analyzed. TLR mRNA expression increased modestly when cultured monolayered cells were stimulated by TNF- α, IL-1 α, IL-1 β, IL-6, IL-8, IFN- γ (about 2-fold), hypoxia (2.1- to 4.8-fold selectively), and wounding (3.1- to 9.3-fold). In airlifted multilayered cells, TLR expression increased 7.8- to 25.9-fold compared to monolayered cells. Airlifted cells showed increased response to low concentrations of lipopolysaccharide (LPS) and peptidoglycan (PGN) stimulation. NF κ B inhibition prevented the formation of cell sheets and led to the collapse of already-formed multilayered structure and the simultaneous reduction of TLR mRNA level. In conclusion, our study showed that the conjunctival epithelial cell expressed TLR was sensitive to various stimulants, and a multilayered epithelium-like structure was needed to maintain TLR expression.